2003
DOI: 10.1001/archpsyc.60.12.1256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Substance Initiation, Use, and Problem Use in Adolescents

Abstract: Background:We conducted a sibling/twin/adoption study of substance initiation, use, and problem use, estimating the relative contribution of genetic and environmental influences on these phenotypes in adolescents. Methods:The participants were 345 monozygotic twin pairs, 337 dizygotic twin pairs, 306 biological sibling pairs, and 74 adoptive sibling pairs assessed by the Colorado Center for the Genetics and Treatment of Antisocial Drug Dependence, Denver and Boulder. The initiation, use, and problem use of tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
259
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(294 citation statements)
references
References 45 publications
29
259
3
3
Order By: Relevance
“…Many studies have demonstrated a familial clustering with alcohol, opiate, and poly-drug dependence (Bierut et al, 1998;Merikangas et al, 1998;Nurnberger et al, 2004;Rhee et al, 2003;Rounsaville et al, 1991). The present report extends this work to the familial aggregation of specific substance use and dependence associated with cocaine dependent subjects.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Many studies have demonstrated a familial clustering with alcohol, opiate, and poly-drug dependence (Bierut et al, 1998;Merikangas et al, 1998;Nurnberger et al, 2004;Rhee et al, 2003;Rounsaville et al, 1991). The present report extends this work to the familial aggregation of specific substance use and dependence associated with cocaine dependent subjects.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous studies of alcohol, opiate, and polysubstance dependence have assessed the clustering of dependence in families. Consistently, relatives of alcohol and drug dependent individuals are more likely to develop substance use disorders than relatives of nondependent subjects (Bierut et al, 1998;Merikangas et al, 1998;Nurnberger et al, 2004;Rhee et al, 2003). Similarly, twin and adoption studies demonstrate that a vulnerability to dependence on multiple substances is transmitted between biologic relatives and is related to genetic factors (Kendler et al, 2003;Tsuang et al, 1998).…”
Section: Familial Contributions To Use and Dependencementioning
confidence: 97%
“…The corresponding heritability estimates under the assumptions of the CTM were consistent with values reported from various twin studies (Carmelli et al, 1992;Heath et al, , 1999Boomsma et al, 1994;Han et al, 1999;Koopmans et al, 1999;Madden et al, 1999Madden et al, , 2004McGue et al, 2000;Rhee et al, 2003;Maes et al, 2006). However, using a novel analysis, which allowed us to adjust for both the smoking status of an individual's friends and the concordance for friends' smoking status within pairs, we found greater concordance for smoking in MZ pairs only at wave 1 when most twins were living together.…”
Section: Discussionsupporting
confidence: 85%
“…Environmental and lifestyle factors shared by twins have been found to play only a small role in adult smoking (Sullivan and Kendler, 1999;Li et al, 2003), although they may be more important in the smoking behaviours of adolescents and young adults (Boomsma et al, 1994;Han et al, 1999;Koopmans et al, 1999;McGue et al, 2000;Hopfer et al, 2003;Rhee et al, 2003;White et al, 2003).…”
mentioning
confidence: 99%
“…Twin studies have demonstrated genetic influences on the liability to develop cannabis dependence in both adults and adolescents (Kendler and Prescott 1998;Tsuang et al 1998;Maes et al 1999;Kendler et al 2000;Miles et al 2001;Lynskey et al 2002;Rhee et al 2003). A logical candidate gene that could influence the liability to develop cannabis dependence symptoms is CNR1, which codes for the cannabinoid receptor.…”
Section: Introductionmentioning
confidence: 99%